MANAGEMENT STRATEGIES FOR CHILDREN WITH SPECIAL NEEDS IN EARLY YEARS - Undiyaundeye, Florence A; A, Basake Julius (PEOPLE: International Journal of Social Sciences, 2018)
All parents want what is best for their children but not every knows how to help children avoid the biggest issues in special children’s behavior problems. Ignorance on the knowledge of handling special need children’s needs can affect these children for the rest of their lives. Teaching children with special needs present teachers with some distinctive challenges. Children with special needs are no longer isolated in special education classrooms. Kids with special needs strive in the presence of their pairs. There are so many lessons that children with special needs can form from other kids and so many friendships to be formed. Children with disorder and other learning disabilities perform better if a classroom is setup to accommodate their special needs. Teacher’s class target is to be creative and also innovative when classroom activities are involved. Managing an inclusive classroom is easier if some personalized teaching strategies for the special needs pupils are carried out. They require exiting activities and revitalizing projects that offer a resourceful curriculum within the structure of the accepted classroom programme. Teachers in a special need classroom need to modify lessons to meet the needs of every pupil in the classroom based on their abilities and carrying capacities.